Correlation Between VEP Latency, CDR and PSD On Standard Automated Perimetry In Newly Diagnosed POAG Cases - Shikha Baisakhiya; Gurdev Lal Goyal; Punita Garg; Zahid Khan (Delhi Journal of Ophthalmology)
Aim and Objective:- The current study was conducted to find out the correlation between Pattern reversal VEP (visual evoked potential) parameters, standard automated perimeter parameters and cup disc ratio (CDR) in newly diagnosed cases of POAG (primary open angle glaucoma). Materials and Methods:- The study included 72 individuals of both the genders. The subjects underwent routine ophthalmic examination of anterior and posterior segment, IOP (intraocular pressure) measurement, visual field testing by Humphery’s automated perimeter and Pattern reversal VEP (visual evoked potential) testing. The subjects were classified into mild, moderate and severe based on MD (Mean deviation). Results:- In our study, the mean PSD (pattern standard deviation) and CDR (cup disc ratio) value increased with increase in the severity of glaucoma. The findings of our study also showed that increased PSD and CDR mirrored with increase in P100, N75 and N145 latency and decrease in P100 amplitude. The PSD was positively correlated with the latencies of VEP and negatively correlated with the amplitude of VEP waves (p<0.001). Conclusion:- We conclude that VEP can be used as a reliable tool for monitoring the progression of glaucoma.